2019
DOI: 10.2106/jbjs.rvw.18.00182
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Observed Sex Discrepancy in the Prevalence of Osteoarthritis

Abstract: When stratified by sex and age, there is a greater age-adjusted prevalence of osteoarthritis in women (23.5%) as compared with men (18.1%).» The discrepancy between males and females in the prevalence of osteoarthritis is likely multifactorial, being related to hormonal, metabolic, structural, and nutritional differences.» Cartilage is lost at a higher rate in women after accounting for confounding variables such as age, body mass index, and bone volume at baseline. » Estrogen replacement therapy diminishes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…With regard to the incidence based on sex, in the general population the prevalence of OA adjusted for age is higher in women than in men. 32,33 Interestingly, our systematic review showed that, among the physically active population, the prevalence of OA is higher in males. This could be explained by the fact that males undertake more intense sporting activities than women, exposing the body and joints to greater stresses and loads.…”
Section: Discussionmentioning
confidence: 91%
“…With regard to the incidence based on sex, in the general population the prevalence of OA adjusted for age is higher in women than in men. 32,33 Interestingly, our systematic review showed that, among the physically active population, the prevalence of OA is higher in males. This could be explained by the fact that males undertake more intense sporting activities than women, exposing the body and joints to greater stresses and loads.…”
Section: Discussionmentioning
confidence: 91%
“…The cellular and molecular mechanisms behind the well-documented sex discrepancy in OA incident rates are poorly understood. Many factors are believed to contribute to the higher incidence and severity of OA in females, such as age, psychosocial status, metabolic variables, hormonal differences, anatomical variations, and inflammatory disease ( Ferre et al, 2019 ). While the focus of many previous studies was mainly on bone shape ( Yang et al, 2014 ; Wise et al, 2016 ; Frysz et al, 2020 ), gait kinematics ( Phinyomark et al, 2016 ; Ro et al, 2017 ; Allison et al, 2018 ), and sex hormones ( Zazulak et al, 2006 ; Brennan et al, 2010 ; Boyan et al, 2013b ; Wang et al, 2013 ; Antony et al, 2016 ), little effort was invested into determining differences in the global transcriptome profile.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have been frequently assessed in the arthroplasty literature largely because women are more likely to develop osteoarthritis due to combined metabolic, hormonal, and structural etiologies. 30 Despite the increased osteoarthritis rates prevalent in women, orthopaedic surgeons are less likely to refer female patients for total knee arthroplasty, 31 and physicians are more likely to attribute pain to psychological causes, 32 which together may lead to presentation at a later disease state.…”
Section: Discussionmentioning
confidence: 99%